ANALISIS DIMENSI EMPLOYER BRANDING DAN REPUTASI PERUSAHAAN UNTUK MENINGKATKAN MINAT PELAMAR (STUDI PADA BANK SINARMAS UNIT USAHA SYARIAH MALANG) - Anggia, Adhitya; Yuniarinto, Agung (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this study is to identify the application of employer branding and company reputation to increase the number of applicant in the Sharia-Compliant Business Unit of Bank Sinarmas in Malang. This descriptive qualitative research uses primary and secondary data acquired from interviews and documentation. The research subjects are employees as key informants and prospective applicants as main informants. The data was analyzed through data reduction, data presentation, and conclusion drawing, while the validity was assessed using source, method, and theoretical triangulation. This study finds that the Sharia-Compliant Business Unit of Bank Sinarmas in Malang does not formally apply employer branding, but it has been implemented according to values of interest, economy, social, development, and usefulness. Furthermore, the business unit has a good reputation, but it is not as good as that of other Islamic banks. This is one of the factors that make prospective applicants have some interest to apply to the Sharia-Compliant Business Unit of Bank Sinarmas, but they do not make the bank as their main priority.